Susceptibility to emotional contagion in health organizations: impact on organizational commitment and intention to stay - Aydemir, Ahmet. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2016., 2016)
Health organizations include varying emotions experienced due to frequent interactions with colleagues and customers. It was thus of interest to investigate which stressors affect organizational outcomes for employees and patients in these organizations. Of particular interest were stressors and their outcomes at workplaces for doctors. For that purpose, drawing from Job Demands-Resources Model and Social Exchange Theory, the study evaluated the influences of workload and emotional labor on organizational commitment, especially affective commitment, and intention to stay. The moderating role of susceptibility to emotional contagion on the relationship between stressors and commitment, and mediating role of commitment on the relationship between stressors and intention to stay were also investigated. The participants included 270 doctors (137 male, 133 female) from six hospitals in the Marmara region in Turkey. Survey methodology was used for data collection. The results indicated that commitment was positively associated with intention to stay. Higher affective and normative commitment were positively related to intentions to stay. Workload was not related to commitment. Emotional labor and deep acting were positively related with organizational commitment. Commitment did not act as a mediator on the relationships between stressors and intention to stay. Susceptibility to emotional contagion and negative affect factor had moderating roles between workload, and affective and organizational commitment, respectively. Though these relationships may exist in various contexts, the focus of the research was on doctors working in hospitals in Turkey. Research including different variables, sample groups, analysis methods and geographical regions may be conducted to further investigate these relationships.
Keywords: Health services administration.; Emotional contagion.; Contagion (Social psychology)